THE INFLUENCE OF INDUSTRIAL WORK PRACTICES, FAMILY ENVIRONMENT AND MOTIVATION ON WORK READINESS - Idris, Ardhy Rifaldy; Marsofiyati; Faslah, Roni (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to: 1) determine the effect of Industrial Work Practices on Job Readiness; (2) knowing the effect of the family environment on work readiness; (3) knowing the effect of motivation on work readiness; (4) determine the effect of Industrial Work Practices, Family Environment, and Motivation on Work Readiness. The population in this study were 179 students at SMKN 16 Jakarta, grade 12 for the academic year 2021-2022. This research uses a quantitative approach with a survey method. The number of samples in this study were 119 respondents. Data collection using a questionnaire. The data were processed using the SPSS 25 program. The results showed that Industrial Work Practices, Family Environment and Motivation had a significant effect on the interest in entrepreneurship partially and simultaneously.